The implementation of carbon tax as an emission reduction instrument policy in the Nordic countries: Pigovian tax effect analysis - Wibowo, Rafly Surya; Naylah, Maal (Educoretax, 2024)
Climate change has caused an urgency to implement regulations in various countries to address the factors that cause climate change. Carbon tax is one of tools to address climate change. Carbon tax is one of implementation of the Pigovian tax that aims to internalize the negative impacts of carbon emissions by imposing a fee on the emissions produced. This research aims to analyze the effect of carbon tax policies and factors that influence carbon emissions in Nordic countries in 2010-2019 using panel data regression with fixed effect model estimation. Economic growth, population growth, renewable energy consumption, and fossil consumption are variables added as control variables in this study. The sample in this study consists of four Nordic countries, namely Denmark, Finland, Norway, and Sweden. The results of the study show that carbon taxes, population growth, and renewable energy consumption have a negative and significant effect on carbon emissions. Then it was found that economic growth and fossil consumption has a positive and significant effect on carbon emissions.